2020
DOI: 10.1002/acr.23892
|View full text |Cite
|
Sign up to set email alerts
|

Supervised Group Exercise in Axial Spondyloarthritis: Patients' Satisfaction and Perspective on Evidence‐Based Enhancements

Abstract: Objective. Supervised group exercise (SGE) has been proven effective in patients with axial spondyloarthritis (SpA), but its contents and dosage do not always comply with current scientific insight. This aim of this study was to describe axial SpA patients' satisfaction with current SGE and perspective on potential evidence-based SGE enhancements.Methods. Patients with axial SpA who participated in SGE in 4 regions in The Netherlands (n = 118) completed a cross-sectional survey on their satisfaction with featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 37 publications
3
54
0
Order By: Relevance
“…Similar to patients without PT, only half of those with PT met the vigorous-intensity PA recommendation. This finding could be related to results from previous studies, showing that appropriately dosed aerobic PA is often not included in (PT) exercise programs [33,34]. A recent study on content of PT in axSpA patients found that in the Netherlands, aerobic exercises are only performed during individual PT in 22% of patients [32].…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Similar to patients without PT, only half of those with PT met the vigorous-intensity PA recommendation. This finding could be related to results from previous studies, showing that appropriately dosed aerobic PA is often not included in (PT) exercise programs [33,34]. A recent study on content of PT in axSpA patients found that in the Netherlands, aerobic exercises are only performed during individual PT in 22% of patients [32].…”
Section: Discussionmentioning
confidence: 61%
“…Ninety-nine patients had PT treatment at the time the study was conducted: 77 had individual PT treatment in a private practice only, 11 participated in axSpA-specific group exercise therapy only and 11 had both individual PT treatment in a private practice and group exercise therapy (on two different days). The group exercise therapy consisted of a standardized program comprising weekly land- and water based mobility and strengthening exercises and sports (mostly volleyball) in most patients [ 34 ]. Table 2 shows the duration, frequency and contents of current individual PT treatment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations